PENGARUH STRUKTUR KEPEMILIKAN, KEAKTIFAN KOMITE AUDIT, DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Sudjatna, Indiferent; Muid, Dul (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to demonstrate empirically that ownership concentration, managerial ownership, Audit comitee activeness, and audit quality have negative significant effect on earning management The population used in this study are all manufacture companies listed on IDX in the period of 2010-2012. The sampling method used in this study was purposive sampling method. The analysis technique in this study uses multiple regression analysis with help from a program named SPSS From the analysis performed in this study, ownership concentration is the only variable that has significants negative effect on earnings management. Meanwhile, managerial ownership, audit comitee activeness, and audit quality have positive effect on earning management.